Accounting for the Global Economy: Is National Regulation Doomed to Disappear? - Bonifasius Hamonangan Tambunan; Budi Anshari Nasution; Halomoan Sihombing; Iskandar Muda (Jurnal Ilmiah Wahana Akuntansi, 2017)
Many observers consider accountancy to be the most international of the professions, but differences between countries as to how they regulate accountancy have resulted in barriers which prevent the profession from meeting the changing needs of an increasingly global economy. This paper examines how the European Union has adopted different approaches to overcoming regulatory divergence, and identifies three approaches which have been followed: regulatory cooperation, regulatory competition and regulatory contracting-out. The relative impact of each method is evaluated. Recent developments at worldwide level (under the auspices of the WTO, OECD and lOSCO) are cited to demonstrate that many of the regulatory reforms in Europe are of growing relevance to the United States, and some of the likely changes which will be required are identified. The need for national systems of regulation to evolve in response to the process of globalisation is underlined, and the paper concludes with an assessment of how the accountancy profession might respond to the challenges and opportunities of the new environment.